The implementation of Islamic Criminal Law in Malaysia: challenges and prospects - Ahmad Termizi bin Abdullah (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2005)
This research entitled "The implementation of Islamic criminal law in Malaysia: challenges and prospects" is written in order to find out the real problems of enforcing the Islamic criminal law in Malaysia and also to give some recommendations on the appropriate approach of implementing it in Malaysia. The concept of Islamic criminal law is explored in brief in order to give the clear framework of the concept of crime in Islam. The researcher further discussed the attempts made by the State of Kelantan and Terengganu in implementing the Islamic criminal law in this country. The comments from various parties are studied in order to identify the problems in implementing the law. The research also discusses some of the issues raised in other countries which had implemented the Islamic criminal law. The research is also embarked in order to know in detail the current situation of Islamic law in Malaysia. This is necessary because the knowledge of the current law practised in Malaysia is important in order to know the appropriate approach to implement the Islamic criminal law. The research then discussed the barriers in implementing Islamic criminal law in this country and proposed some suggestions on the amendment of the Malaysian laws including the Federal Constitution to make them in line with Islamic law. Besides, this research also examined the weaknesses of Islamic judiciary system in Malaysia and the ways of its improvement. This is including the discussion on the suggestion on appointment of women as Syariah Court judge in Malaysia in order to improve the administration of Syariah Court as well as to improve the good reputation of the court. Finally, it also discussed some of the efforts made by the Malaysian government in implementing Islam in this country.